Road Safety in South Asia : Opportunities for Shared Regional Initiatives - World Bank (World Bank, Washington, DC, 2020)
There is an increasing recognition that policy initiatives at the regional level can complement and strengthen country road safety strategies and programs. This is certainly the case in the South Asia region, with implications for regional road safety investment priorities and potential for shared road safety initiatives.